2007
DOI: 10.1249/mss.0b013e318053e7a2
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity, Growth, and Inflammatory Mediators in BMI-Matched Female Adolescents

Abstract: The normal-weight, physically active group was fitter and had greater lean body mass, stronger bones, and lower levels of inflammatory markers than did the normal-weight, sedentary group. In adolescent girls, the choice of a lifestyle involving high school sports is characterized by a circulating mediator and body composition pattern that, if sustained, is associated with generally lower long-term risk of cardiovascular disease and osteoporosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
70
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(77 citation statements)
references
References 30 publications
6
70
1
Order By: Relevance
“…11,17 In addition, several of these studies did not control for body fat or CRF in their analyses, [27][28][29] or if they did so, the associations became attenuated or non-significant. 30,31 We also showed that CRF was inversely associated with CRP, C3 and C4.…”
Section: Modelmentioning
confidence: 99%
“…11,17 In addition, several of these studies did not control for body fat or CRF in their analyses, [27][28][29] or if they did so, the associations became attenuated or non-significant. 30,31 We also showed that CRF was inversely associated with CRP, C3 and C4.…”
Section: Modelmentioning
confidence: 99%
“…Intense and moderate exercises were also used 18,19,24,[30][31][32][33] planned exercises and sports games 29 and controlled exercises in exercise bike 31 besides sedentary behavior evaluation 20 . Longitudinal studies also assessed cardiorespiratory fitness by different methods: ergospirometry test 29 , 20 m shutle-run test 9 and cardiorespiratory test on exercise bike 32,33 . A study has used indirect calorimetry test for evaluating metabolic rate 19 .…”
Section: Resultsmentioning
confidence: 99%
“…A study has used indirect calorimetry test for evaluating metabolic rate 19 . It was observed that 10 articles were selected with cross-sectional design, among them, five showed a relationship between physical activity level, body composition and cardiometabolic markers 12,23,25,[32][33][34][35][36] ( Table 2). Two studies showed an association between sedentary behavior and cardiometabolic markers 25,34 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…low CTX/OC ratio) for both parity groups. This low CTX/OC ratio may be caused by a changed nutrient requirement, influences of dietary intake (increased from beginning to mid-gestation: 2.3 to 2.6 kg), skeletal replenishment or bone mass compensation in multiparous sows, and the increased activity during group housing, because it seems that exercise increases bone formation as has been found in humans (Ischander et al, 2007;Counotte et al, 2009).…”
Section: Discussionmentioning
confidence: 98%